The Sex Education Method in Agrarian Communities - Desriani Desriani; Sofa Muthohar; Lilif Muallifatul Khorida Filasofa; Mursid Mursid (Pusat Studi gender dan Anak (PSGA) Universitas Islam Negeri Walisongo Semarang, 2021)
Sex education is an important thing that must be taught appropriately to children, but some people still think that sex education is taboo for children to know, and they let them alone to learn. The purpose of this study is to describe how an agrarian society provides sex education. This research is qualitative research with an ethnographic research type. The results show that 1) The community uses fiqh (rituals of worship) learning methods to cover genitalia and teach the culture of shame from an early age. 2) People still feel it taboo to mention genitals directly. So, they use other terms that are considered not to stimulate crime and are more polite, namely to refer to the penis as sunik, gentog and anu, while the vagina is replaced with the terms memek, iwak kebo and anu. 3) People still use the circumcision method for women even though, World Health Organization (WHO) has stated it is prohibited. This study recommends the government and community leaders continue to carry out sex education for children with the correct method according to health, religion, human rights, and laws.